FACTORS AFFECTING THE FINANCIAL PERFORMANCE OF ISLAMIC INSURANCE COMPANIES IN INDONESIA USING SURPLUS ON CONTRIBUTION (SOC) - Kamaruddin Kamaruddin; Zuhrinal M Nawawi; Andri Soemitra (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Sharia-based insurance companies and businesses began to move faster in the last 10 years in Indonesia, along with the development of the sharia finance industry in general, such as sharia banks, sharia cooperatives and others. Since the establishment of this type of sharia insurance company in Indonesia at the end of 1994 with the product Takaful Family Insurance (life insurance). Sharia insurance has begun to be recognized by Muslim and non-Muslim communities to meet the need for insurance services that are increasingly felt by individuals and the business world in Indonesia. Insurance is a financial means in managing household life, both in facing the fundamental risks or in dealing with risks to the assets owned. The healthy impact of business and service companies such as sharia insurance is monitored by its financial performance. Either it is measured by Surplus On Contribution (SOC) or Return on Assets (ROA). This article tried to analyze the factors that affect the financial performance of Islamic Insurance companies in Indonesia, for the last 5 (five) years period, by including several positive and negative factors. The factors that the authors recommended in this analysis were Company size, Leverage, Liquidity, Tangibility, Volume of Capital, and Loss Ratio. The approach model for this analysis used a path model approach (Path Model's) with the assumption that each of the factors involved has a causal relationship with one another. So that the advantage of using this approach was its results will be able to give the direct or indirect effects of each factor on the financial performance to be analyzed.